Integrating Digital Literacy in EFL Teaching and Learning Contexts: A Systematic Literature Review - Sudirman, Anselmus (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This article aims to identify (a) the incorporation of digital literacy in EFL classrooms that reinforce student engagement, language acquisition, and teaching practices, (b) the main challenges encountered by teachers and students in the implementation of digital literacy strategies and (c) their implications practices in English as a Foreign Language (EFL) teaching and learning contexts. This systematic literature review draws on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework for analyzing 20 out of 800 articles concerning digital literacy in the EFL context, published in indexed journals such as Google Scholar, Scopus, and Web of Science from 2020 to 2025. The results show the improvements in student engagement and language acquisition facilitated by digital tools, highlighting the advantages of technologies like digital media platforms, game-based learning, and online resources in promoting interactive and motivating learning experiences. The analysis identifies significant challenges, such as inadequate digital infrastructure, limited access to technology, and insufficient teacher training, which impede the effective implementation of digital literacy strategies in EFL instruction.  This review enhances the understanding of digital literacy within EFL education, facilitating the development of more effective and inclusive teaching practices in the digital era.